OPTOELECTRONIC DEVICE CONVERTING SECONDARY HEAT INTO LIGHT (Scientific journal of the Fergana State University, 2024)
A project has been developed for an optoelectronic compact energy-saving device that uses secondary heat, that is, body temperature, using special thin chalcogenide films. It has been proven that such a device can be fabricated using multilayer dielectric structures prone to optical anisotropy of p-n junctions observed in inhomogeneous compositions of thin chalcogenide films. In this article, inhomogeneous cluster-type thin films in thin chalcogenide films are determined by the current-voltage method. The presence of cluster segregation is confirmed with an uneven distribution of inclusions of atoms of the stoichiometric composition of thin films of chalcogenides.